Generating Meta-Model-Based Freehand Editors - Minas, Mark (Electronic Communications of the EASST, 2007)
Most visual languages as of today (e.g., UML) are specified using a model in a meta-model-based approach. Editors for such languages have supported structured editing as the only editing mode so far. Free-hand editing that leaves the user more freedom during editing was not supported by any editor or editor framework since parsing has not yet been considered for meta-model-based specifications. This paper describes the diagram editor generator framework DiaMeta that makes use of meta-model-based language specifications and supports free-hand as well as structured editing. For analyzing freely drawn diagrams, DiaMeta parses a graph representation of the diagram by solving a constraint satisfaction problem.